HOW DOES SELF-EFFICACY AFFECT PERFORMANCE OF LEARNER? - Vakani, Farhan; Sheerani, Mughis; Afzal, Azam; Amin, Almas (Journal of Ayub Medical College Abbottabad, 2012)
All types of attribution based on which learners make their judgement (i.e., self efficacy), about academic success or failure or about a specific task usually affect their performance and their capabilities to deal with different realities.1 It is perhaps the most distinctive capability of selfreflection. Many of the cognitive theorists have defined it as a meta-cognitive capability. This judgement influence learners choose what to do, how much effort to be invested in the activity, how long to carry the phase of disappointment, and whether to approach the task anxiously or with assurance.